Managing knowledge sharing in distributed innovation from the perspective of developers: empirical study of open source software projects in China. Issue 1 (2nd January 2017) - Chen, Xiaohong; Zhou, Yuan; Probert, David; Su, Jun
ABSTRACT: Knowledge sharing is the key factor that influences the performance of open source software (OSS) projects, which are the representative cases of distributed innovation. This paper aims to explore the mechanism of knowledge sharing in OSS projects from the perspective of developers in China. A quantitative method with the analysis of 403 valid questionnaires is adopted. A series of hypotheses about how distributed innovation (independent variables) influences knowledge sharing (mediating variable) and then affects the performance of OSS projects (dependent variable) are tested and approved. On the one side, we argue that developers will actively affect knowledge sharing in terms of participative motivation, social network and organisational culture. On the other hand, users may also affect the knowledge sharing when considering innovation willingness and capacity. It is interesting to find that social network is the most important factor in Chinese cases. It is strongly recommended to strengthen the collaboration between software companies and OSS communities.